Thai small business owner leasing customer trust: A SEM analysis - Suvitsakdanon, Udom; Sornsaruht, Puris (My University, 2019)
Systematic random sampling was used to obtain the study's 303 small business leasee sample. The CFA and SEM analysis used LISREL 9.10 from which it was concluded that all of the variables affecting a Thai small business leasing company's customer trust were positive. The causal variables influencing customer trust, from highest to lowest, were service quality (SQ), corporate social responsibility (CSR), customer satisfaction (SAT), and socioeconomic status (SES) with total influences of 0.80, 0.76, 0.64 and -0.14 respectively.
Keywords: Corporate social responsibility; Service quality; Small-medium enterprises; Thailand